Implementasi Nilai Keislaman Pada Kegiatan Studi Kenal Alam Dan Lingkungan MTsN 9 Kediri - Vegita Nur Bidayasari; Moh. Irmawan Jauhari; M. Arif Khoiruddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
MTsN 9 Kediri in implementing the study activity program knows nature and the environment in several areas in besides that the main purpose is to refresh the spirit of learning and also instill Islamic values. The focus of research in this article is to describe, the islamic value implemented during the study of nature and the environment at MTsN 9 Kediri, efforts in applying Islamic values to the behavior and attitudes of students when conducting study activities to know nature and the environment, the implications faced in integrating Islamic values in study activities to know nature and the environment at MTsN 9 Kediri. This research is a qualitative research. Data collection techniques used observation, in-depth interviews, and documentation. The results of the study, namely: (1) Islamic values that are implemented during the study of nature and the environment at MTsN 9 Kediri are first Faith: tawheed, shukr, du’a and tawakkul, maintaining trust. Second Shari’ah: selection of tourist destinations, shari’ah accommodation, honest transactions. Third, Morals: Honesty and integrity, patience and tolerance, respect for the environment and cleanliness. (2) Efforts in applying Islamic values: Faith which can be done on belief in Allah, Shari’ah which can be instilled regulating the relationship between Allah and humans, morals by instilling good moral ethics. (3) The implications and intergration of Islamic values in this activity are to monotheize nature, provide natural space to strengthen faith, shari’ah, and morals. As well as expanding the knowledge and experience of students in learning outside the school environment.